Implementasi Projek Penguatan Profil Pelajar Pancasila (P5) dalam Meningkatkan Kemampuan Sikap Mandiri Siswa Sekolah Dasar - Gusty Ekka Fajaryna; Ujang Jamaludin; Damanhuri (Universitas Cokroaminoto Palopo, 2024)
The urgency of the problem addressed in this research lies in the fact that many students still lack independent attitude skills. This issue became evident during the implementation of the Pancasila student profile strengthening project at SDN Cikerut. According to pre-research interviews, SDN Cikerut carried out three themes for the Pancasila student profile strengthening project, each of which targeted the independence dimension as one of the key areas of focus. Independence is one of the most important characteristics an individual can possess. The development of an independent attitude is directly linked to the formation of self-identity. This attitude fosters self-reliance, confidence, and self-control over one's thoughts, emotions, and actions. For students, independence plays a critical role in their academic journey, as those who learn independently are able to achieve their educational goals without relying on assistance from peers. Consequently, these learners become responsible not only for their learning process but also for the outcomes of their studies. To cultivate this independent attitude, schools must provide various forms of support. One key support involves educators facilitating activities that encourage students to develop their independence. At SDN Cikerut, one of the primary efforts to foster independent character is through the implementation of a Pancasila student profile strengthening project. This study was conducted to support the project's goal of enhancing students' independent attitudes. The research utilized a descriptive method through a qualitative approach, conducted at SDN Cikerut in Cilegon City. The study subjects included the Principal, Grade V teacher, and Grade V students. Data was collected through observation, interviews, and documentation. The analysis involved data reduction, presentation, and conclusion drawing. The findings showed that the project successfully improved the independent attitude of Grade V students. Challenges that arose during implementation were effectively addressed by the teachers.